Prevalence of Glucose-6-Phosphate Dehydrogenase (G6PD) Deficiency among Neonates with Jaundice in a Tertiary Hospitalin Nigeria (Journal of Basic and Applied Research in Biomedicine, 2022)
G6PD deficiency is known to be associated with neonatal jaundice, kernicterus and even death. G6PD is the first enzyme of the pentose phosphate pathway and catalyzes the conversion of glucose-6-phosphate to 6-phosphogluconolactone, with the concomitant reduction of nicotinamide adenine dinucleotide phosphate (NADP) to its reduced form (NADPH). Three hundred and twenty five neonatal blood samples were collected for the study between the ages of 1–10days of both sexes. About 4ml of blood sample was collected from newborn baby with jaundice, 2ml of blood sample was dispensed into di-potassium ethylenediaminetetracetic acid (K2EDTA) bottles for packed cell volume and haemoglobin estimation using haematology analyzer (sysmex model KX-21N) also K2EDTA blood sample was used for G6PD status determination, remaining 2ml of blood sample was dispensed into heparin bottles for bilirubin estimation. Out of 325 newborn babies with neonatal jaundice, 96(29.5%) were G6PD deficient; 57 were male and 39 were female. Mean± SD of total bilirubin (B1) andconjugated bilirubin(B2) were significantly (P